TELAAH TENTANG PEMAHAMAN BUDDHA SEBAGAI PEMIMPIN SPIRITUAL, BUKAN ENTITAS ILAHI - Sumanggala, Kadek Jaya; Firnadi, Aryanto; Saputro, Uung Gondo (Dharmasmrti: Jurnal Ilmu Agama dan Kebudayaan, 2024)
There are still many people who think that the Buddha is God or a Prophet, Buddhists worship idols. This is due to a lack of a correct understanding of the Buddha's personality. This research aims to describe textual information and answer some questions related to the personality of the Buddha based on the Buddhist holy book, namely Tipi?aka. The research uses a qualitative approach from various Tipitaka literature, journals, and books that are by the topic of discussion. The concept of omnipotence is the origin of the emergence of God. God is understood as the principle of limitation and gives limits to actuality. The Buddha was born in Northern India, lived a life of learning from learned teachers and attained enlightenment by understanding and realizing the Four Noble Truths. Then from then on, he became a Buddha. The Buddha taught the Dhamma to his disciples (gods and humans) and founded a community known as the Sangha. Buddha has qualities that distinguish him from other human beings, namely three knowledge, six superpowers, and ten powers. The concept of God in Buddhism is not personified and Buddhists are more focused on attaining Nibb?na.